Ranunculus magniflorus sp. nov. and R. irregularifrons sp. nov., (Ranunculaceae), two new species of the R. auricomus complex in Romania - Dunkel, Franz G. (Phytotaxa, 2024)
Two new species of the Ranunculus auricomus complex of Romania with undivided basal leaves are described and depicted: according to flow cytometry measurements, Ranunculus magniflorus Dunkel is a diploid species with large flowers and petals up to 20 mm, the lowermost cauline leaf segments are undivided (var. magniflorus) or have 2–8 short or long and patent teeth (var. dentatus). The taxon occurs at the Banat Mountains, at southern border of the Southern Carpathians and in adjacent Serbia. R. irregularifrons is a tetraploid species characterised by an irregularly und acutely serrated leaf edge of the final leaves. To present knowledge, it is restricted to the Banat Mountains.